2003
DOI: 10.1002/chem.200390169
|View full text |Cite
|
Sign up to set email alerts
|

Chalcogenide‐Lewis Acid Mediated Reactions of Electron‐Deficient Alkynes with Aldehydes

Abstract: Reactions of but-3-yn-2-one (2) with aldehydes 1 in the presence of a Lewis acid and dimethyl sulfide (3 a) predominantly gave (E)-alpha-(halomethylene)aldols 4-5 in high yields, while reactions of methyl propiolate (6 a) mainly afforded (Z)-3-halogeno-2-(hydroxymethyl)acrylates 7-8 in low to moderate yields. A reaction of dimethyl acetylenedicarboxylate (10) with 1 a in the presence of TiCl(4) and 1,1,3,3-tetramethylthiourea (3 c) produced maleate (E)-11 (40 %) and butenolide 12 (40 %). When a reaction of 6 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 75 publications
(15 reference statements)
0
16
0
Order By: Relevance
“…[105] Vinyl sulfides have been used as masked carbonyl compounds. [106] 2-Ethynyl-3-phenyloxirane (12, R 1 = Ph); Typical Procedure: [102] To a stirred mixture of the hydroxy sulfide 11 (100 mg, 0.394 mmol) in CH 2 Cl 2 (8 mL) was added Me 3 OBF 4 (66 mg, 0.435 mmol). The mixture was kept at rt for 8 h, before a soln of 7% aq NaOH (5 mL) was added, and the resulting mixture was stirred for 20 min.…”
Section: Variation 5: Amide Derivatizationmentioning
confidence: 99%
“…[105] Vinyl sulfides have been used as masked carbonyl compounds. [106] 2-Ethynyl-3-phenyloxirane (12, R 1 = Ph); Typical Procedure: [102] To a stirred mixture of the hydroxy sulfide 11 (100 mg, 0.394 mmol) in CH 2 Cl 2 (8 mL) was added Me 3 OBF 4 (66 mg, 0.435 mmol). The mixture was kept at rt for 8 h, before a soln of 7% aq NaOH (5 mL) was added, and the resulting mixture was stirred for 20 min.…”
Section: Variation 5: Amide Derivatizationmentioning
confidence: 99%
“…Although the use of Ti(IV) in Michael-type reactions has been known for almost forty years 12 with important applications in organic synthesis, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] the number of mechanistic studies on such reactions is limited. [18][19][20][21][22][23][32][33][34][35][36][37][38][39] This study might contribute to elucidation of the trimolecular Scheme 1 TiCl 4 -promoted trimolecular condensation.…”
Section: Introductionmentioning
confidence: 97%
“…[1] This reaction proceeded quickly, so the main defect of the Morita-Baylis-Hillman reaction [2] -its very slow reaction rate-was alleviated, so our reaction can be utilized as an alternative to the MoritaBaylis-Hillman reaction. During the course of our study we found that a chalcogenide caused the intramolecular Michael addition in the presence of a Lewis acid [3] and that a thioketone [4] or a thioamide [5] group worked as a catalyst. On the other hand, it is well known that N-unsubstituted thioamides undergo Michael additions with a,b-unsaturated carbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%